2023
DOI: 10.1186/s12877-023-03727-2
|View full text |Cite
|
Sign up to set email alerts
|

A non-randomised controlled study to assess the effectiveness of a new proactive multidisciplinary care intervention for older people living with frailty

Abstract: Background Integrated care may improve outcomes for older people living with frailty. We aimed to assess the effectiveness of a new, anticipatory, multidisciplinary care service in improving the wellbeing and quality of life (QoL) of older people living with severe frailty. Methods A community-based non-randomised controlled study. Participants (≥65 years, electronic Frailty Index ≥0.36) received either the new integrated care service plus usual ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This study is part of a larger nonrandomized trial of the service, with evaluation of symptoms and quality-of-life at baseline, 2 to 4 weeks, and 10 to 14 weeks. 12 In addition to this trial, an experience survey was conducted, with in-depth interviews with a sample of survey respondents. This paper reports the free-text survey responses and interview findings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is part of a larger nonrandomized trial of the service, with evaluation of symptoms and quality-of-life at baseline, 2 to 4 weeks, and 10 to 14 weeks. 12 In addition to this trial, an experience survey was conducted, with in-depth interviews with a sample of survey respondents. This paper reports the free-text survey responses and interview findings.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted within a novel integrated care service located in Hull, England, UK. This new integrated care service is described in full elsewhere, 12 but included a comprehensive assessment and care plan provided by a specialized multidisciplinary team, with a free lunch during a 3 to 5 h single appointment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conducted research has shown that FRED games are an effective technical solution to reduce the risk of vulnerability [23]. In some studies, several scales and questionnaires were used for diagnosis [24][25][26][27][28][29][30].…”
Section: Pilot Pubmed Searchesmentioning
confidence: 99%